تطبيق معادلتي إلوفيتش وفرندليش الأسية في دراسة حركية إزاحة بعض العناصر المعدنية من قبل كربونات الكالسيوم "الصنعية" - عجيب علي (Latakia University Journal -Biological Sciences Series, 2019)
100 mgs of synthetic calcium carbonate were suspended into 50 ml containing an initial quantity of Mn, Zn, Cd or Pb: 3.1 mg of Mn as MnSO4.2H2O, or 3.2 mg of Zn as Zn(NO3)2 or 35 mg of Cd as Cd(NO3)2, or 125 mg of Pb as Pb(NO3)2. The suspension was agitated at the ambient temperature (23-25oC) for a period of time ranging between 2 and 240 minutes, before being filtered to measure the concentration of metallic ions in the filtrates by atomic absorption spectrophotometry. The data were treated by the use of two kinetic models: Elovich and Freundlich power-like. We found out that experimental results fitted nearby equally with both Elovich and Freundlic power-like equation. The uptake kinetic of Pb appeared poorly fitted with the two models. It was succeeded by Cd retention. The uptake kinetics of Mn and Zn were well fitted with the two models. درست حركية إزاحة أربعة عناصر معدنية هي: المنغنيز والزنك والكادميوم والرصاص من قبل كربونات الكالسيوم الصنعية. وكان ذلك بمعاملة 100 مغ من مسحوق الكربونات بحجم ثابت (50 مل) من محلول أحد العناصر المذكورة لفترة زمنية تراوحت مابين 2 - 240 دقيقة. وضعت العينات خلال الفترة المذكورة للرج الهادئ على درجة حرارة المخبر، ثم رشحت وقيست تراكيز العناصر المعدنية في الرشاحات باستعمال جهاز الامتصاص الذري. طبقت معادلتا إلوفيتش وفرندليش الأسية في دراسة المنحنيات الحركية لإزاحة العناصر الأربعة، وأظهرت نتائج تحليل المعطيات التجريبية مقدرة متقاربة لهذين النموذجين الحركيين على التنبؤ بحركية إزاحة العناصر الأربعة وتوصيفها. كانت حركية امصاص الرصاص من أقل الحركيات استجابة للنموذجين، تلاه في ذلك الكادميوم، ولكن بفارق واضح. وأما المنغنيز والزنك، فكانت استجابة حركيتهما للنموذجين على السواء عالية.